Dinamika Idiologi Perempuan dalam Kumpulan Cerpen Luh-Luh Karya I Made Suarsa - I Ketut Sudewa; I Made Suarsa (Journal Social and Humaniora, 2018)
Various ideologies are expressed by the author in the literary works he created. One of the modern Balinese literary authors, I Made Suarsa in his short story entitled Luh-Luh reveals the dynamics of female ideology. The dynamics of women's ideology reflect the ideology of Indonesian women from various professions and are expressed by authors in various styles of language. The problems discussed in this research are: (1) how the dynamics of women's ideology in the story of Luh-Luh short story by I Made Suarsa; and (2) how the author discloses the woman's ideology in her story collection. Theories used to answer the above problems are feminist theory, ideology, and sociology of literature. The research method used is qualitative method through literature study, descriptive analytics, and descriptive. Techniques used are techniques of referring, notes, and tafseer. The results show that women's ideology is seen from three professions, namely: politician (legislative), artist, and state official (executive). The dynamics of women's ideology are expressed by the author through the style of metaphorical language, pleonasm, and comparison. In addition, the author also uses sound games to reinforce the image the author wishes to convey.